Practical or theoretical persistence?: The investigation of (f)actors influencing students’ persistence at three levels - Karolina Eszter Kovacs; Agnes Reka Dusa; Zsofia Kocsis; Pallay Katalin; Timea Szucs; Jozsef Palfi; Kovács Karolina Eszter; Dusa Ágnes Réka; Kocsis Zsófia; Szűcs Tímea; Pálfi József; Поллоі Каталін (Akadémiai Kiadó, 2019)
Abstract. Higher educational dropout is a major education policy issue that can be influenced by several factors. In addition to the family background, it is necessary to mention the motivation for further education as an individual factor which has a complex effect. Another possible individual cause can be the attractiveness of the labor market. Due to the ratio of students dropping out of higher education in Hungary, it can be suspected that students’ intensive work contributes to weaker learning outcomes, resulting dropout finally. In this context, however, the decisive role of the different work values and working attitudes is also unquestionable. Other institutional factors such as the country of the institution or the type of financing of the training cannot be ignored as well. Accordingly, in our research, we investigated individual, institutional, and sociodemographic factors affecting persistence through the TESCEE 2015 (N = 2015) database. Factors influencing persistence were measured by linear regression analysis with the application of two-sample t-test to measure the between-group differences. Regarding socio-demographic factors, the father’s educational level showed a significant impact on a negative while the mother’s employment in a positive way, furthermore, gender presented a trend effect. Institutional factors by themselves are not remarkable; however, some individual factor can increase their impact. At the individual level, the significant effect of career office membership and work values could be detected. Our results can contribute to the recognition of the relationships behind the high ratio of dropout and the identification of factors that can promote persistence, which can support to reduce the dropout ratio at a national and international level.
https://akademiai.com/doi/full/10.1556/063.9.2019.1.22
Keywords: persistence; dropout; student employment; work values; learning motivation